2014
DOI: 10.1088/1748-6041/9/3/035007
|View full text |Cite
|
Sign up to set email alerts
|

In vitroevaluation of a multispecies oral biofilm on different implant surfaces

Abstract: Biofilm accumulation on implant surfaces is one of the most important factors for early and late implant failure. Because of the related clinical implications, the aim of this in vitro study was to compare the bacterial cell attachment of a four-species oral biofilm on titanium discs of purity grade 2 and 4, with machined surfaces and etched-thermochemically modified with Avantblast®. The in vitro biofilm model was composed of early (Actinomyces naeslundii, Streptococcus gordonii), secondary (Veillonella parvu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 47 publications
(73 reference statements)
2
29
0
2
Order By: Relevance
“…An in vitro study compared the bacterial adhesion of a four-species oral biofilm on different purity of titanium discs of grades cp-2 and cp-4, namely Tigr2-c (cp-2, machined surface), Tigr2-t (cp-2, modified surface with Avantblast s ), Tigr4-c (cp-4, machined surface) and Tigr4-t (cp-4, modified surface with Avantblast s ). A significantly higher total bacterial biomass on both cp-4 titanium surfaces was reported [82]. Although the study did not explain in detail, it may be that the higher oxygen content during the processing of cp-4 increased the availability of -OH groups and promoted more bacterial adhesion.…”
Section: Titanium Puritymentioning
confidence: 71%
“…An in vitro study compared the bacterial adhesion of a four-species oral biofilm on different purity of titanium discs of grades cp-2 and cp-4, namely Tigr2-c (cp-2, machined surface), Tigr2-t (cp-2, modified surface with Avantblast s ), Tigr4-c (cp-4, machined surface) and Tigr4-t (cp-4, modified surface with Avantblast s ). A significantly higher total bacterial biomass on both cp-4 titanium surfaces was reported [82]. Although the study did not explain in detail, it may be that the higher oxygen content during the processing of cp-4 increased the availability of -OH groups and promoted more bacterial adhesion.…”
Section: Titanium Puritymentioning
confidence: 71%
“…; Violant et al. ). Conversely, modified titanium surfaces were found to prevent early bacterial attachment (Violant et al.…”
Section: Discussionmentioning
confidence: 99%
“…Implant surface modifications could impact bacterial attachment to titanium (Violant et al. ). Earlier studies found similar influence on early bacterial colonization between titanium, hydroxyapatite, and amalgam (Leonhardt & Dahlen ; Leonhardt et al.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 There are plenty of studies in literature assessing the influence of titanium implant surface characteristics on biofilm formation. [20][21][22][23][24][25][26] In particular, increase in surface roughness and surface free energy seems to facilitate biofilm formation, although this conclusion is derived from largely descriptive literature. 11 As detailed and precise information, as it permits the direct visualization and quantification of living biofilms in their natural hydrated state.…”
Section: Discussionmentioning
confidence: 99%